Pore-fluid Fe isotopes reflect the extent of benthic Fe redox recycling: Evidence from continental shelf and deep-sea sediments - Homoky, W; Severmann, S; Mills, R; Statham, P; Fones, G (2009)
Pore-fluid Fe isotopes may be a unique tracer of sediment respiration by dissimilatory Fe-reducing bacteria, but to date, pore-fluid Fe isotope measurements have been restricted to continental shelf settings. Here, we present δ56Fe values of pore fluids from two distinct sedimentary settings: (1) a riverine-dominated site on the northern California margin (Eel River shelf; 120 m water depth) and (2) biogenic opal-rich volcaniclastic deep-sea sediments from the Southern Ocean (north and south of the Crozet Plateau; 3000-4000 m water depth). The Fe isotope compositions of Crozet region pore fluids are significantly less fractionated (δ56Fe = +0.12‰ to -0.01‰) than the Eel River shelf (δ56Fe = -0.65‰ to -3.40‰) and previous studies of pore-fluid Fe isotopes, relative to average igneous rocks. Our data represent the first measurements of Fe isotope compositions in pore fluids from deep-sea sediments. A comparison of pore-fluid δ56Fe with the relative abundance of highly labile Fe in the reactive sedimentary Fe pool demonstrates that the composition of Fe isotopes in the pore fluids refl ects the different extent of sedimentary Fe redox recycling between these sites. © 2009 Geological Society of America.